Leaving Home with a Partner - Samuel Bentolila; Ildefonso Mendez; Francisco Maeso (Center for Economic Studies and ifo Institute (CESifo), 2015)
Leaving the parental home is often a decision made together by two people. In this paper we present a theoretical model analyzing moving out as a joint decision and then test its implications using a new dataset of university graduates collected in the southern Spanish region of Murcia in 2004-2006, which includes information on partners and their parents. In equilibrium we find some evidence of the importance of assortative mating in moving out. Studying partnership, work, and moving out decisions simultaneously we obtain that the latter depend positively on own human capital and they are affected differently by maternal and paternal characteristics and with different effects on men and women.
Keywords: D84; J12; J13; 330; moving out; employment; assortative mating; job security